2021
DOI: 10.3389/fcell.2021.698190
|View full text |Cite
|
Sign up to set email alerts
|

RAVE and Rabconnectin-3 Complexes as Signal Dependent Regulators of Organelle Acidification

Abstract: The yeast RAVE (Regulator of H+-ATPase of Vacuolar and Endosomal membranes) complex and Rabconnectin-3 complexes of higher eukaryotes regulate acidification of organelles such as lysosomes and endosomes by catalyzing V-ATPase assembly. V-ATPases are highly conserved proton pumps consisting of a peripheral V1 subcomplex that contains the sites of ATP hydrolysis, attached to an integral membrane Vo subcomplex that forms the transmembrane proton pore. Reversible disassembly of the V-ATPase is a conserved regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 104 publications
(179 reference statements)
0
27
0
Order By: Relevance
“…This suggests that RILP is dispensable for V-ATPase assembly in response to mTORC1 inactivation. Next, we examined DMXL1/2, which appear to be functionally related to the yeast V-ATPase assembly factor, the RAVE complex 25 . Genetic ablation of DMXL1/2 strongly suppressed lysosomal V1B2 and cresyl violet levels under basal and mTORC1-inhibited conditions (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that RILP is dispensable for V-ATPase assembly in response to mTORC1 inactivation. Next, we examined DMXL1/2, which appear to be functionally related to the yeast V-ATPase assembly factor, the RAVE complex 25 . Genetic ablation of DMXL1/2 strongly suppressed lysosomal V1B2 and cresyl violet levels under basal and mTORC1-inhibited conditions (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the molecular level, V-ATPase assembly has been studied primarily in yeast, where the RAVE complex binds cytosolic V 1 domains and catalyses their assembly with membrane-bound V o domains. In mammalian cells, several proteins have been implicated in V-ATPase assembly, including DMXL1/2, which appear to be functional equivalents of yeast RAVE 25 . V-ATPase assembly and disassembly is controlled by metabolic signals.…”
Section: Discussionmentioning
confidence: 99%
“…This region of Rav1 is critical for recruitment of RAVE to the vacuolar membrane, as mutations in a small conserved sequence in the center completely prevent recruitment (Jaskolka & Kane, 2020). The RAVE complex has been proposed to template reassembly of the V-ATPase, and the proximal end of Vph1NT may be a “landing site” for the RAVE complex bearing the V 1 subcomplex and subunit C that could then orient the complexes for reassembly of the active complex (Jaskolka et al, 2021). Binding of RAVE to the proximal end of Vph1NT could leave the distal end free to assemble a quaternary complex with the foot domain of subunit C and the appropriate EG peripheral stalk, which is likely to be a critical step in reassembly (Oot et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ju-Hyun Lee et al showed that presenilin-1 (PS1) knockout impairs the orientation of v-ATPase V0a1 subunit to the lysosome (Lee et al, 2010). Michael C. Jaskolka et al found that the prokaryotic RAVE and eukaryotic Rabconnectin-3 complexes facilitate the recombination of V1 with V0 during glucose recovery and consequently restore ATPdriven proton transport (Jaskolka et al, 2021). Qing Tang et al reported the absence of the N-deacetylase and N-sulfotransferase 3 (NDST3) promotes the assembly of the V-ATPase holoenzyme on the lysosomal membrane (Tang et al, 2021).…”
Section: Coupling Efficiency Of V-atpase Pumpmentioning
confidence: 99%